Three Policy Options for Crown Financial Policy - Eric Hansen (New Zealand Government, The Treasury, 2003)
Crown financial policy is concerned with how the government manages the Crown's assets and liabilities. The recently established New Zealand Superannuation Fund, which is projected to grow to around 45% of GDP over the next few decades, highlights that Crown financial policy is likely to become an important economic policy tool with potentially significant implications for New Zealand economic welfare. Previous work has identified that four objectives should form the main basis for assessing alternative Crown financial policies. Three of the objectives relate to minimising distortionary taxation, time-inconsistency of policy and agency cost of government. However, the absolute and relative importance of these objectives is subject to considerable uncertainty. The fourth objective, which is to avoid exacerbating any existing inefficiencies or creating any new ones, is considered part of the baseline common to all policies. In this paper a qualitative analysis is conducted to select three high-level policies for detailed quantitative analysis in future papers. The three policies vary in terms of level of risk: A low risk policy that places emphasis on time-consistency and agency cost issues while down-weighting the significance of distortionary taxation; A medium risk policy that applies a balanced weighting to the three issues; and A high risk policy that places emphasis on distortionary taxation while downweighting time-consistency and agency cost. Detailed policy targets are specified for the candidate policies in terms of Crown net worth, overall risk/return properties of the Crown balance sheet, and the level and structure of financial assets and public debt. The policy targets under the status quo are presented for comparative purposes.
Keywords: E61; H11; H63; 330; Agency cost of government; Bayesian decision theory; comparative institutional method; Crown balance sheet; public debt management; distortionary taxation; time-inconsistency of policy